2023
DOI: 10.1111/ejh.13932
|View full text |Cite
|
Sign up to set email alerts
|

Persistent decreased bone marrow CD3+CD56+ T lymphocytes are inversely associated with mature granulocytes in myelodysplastic syndromes

Abstract: Leone et al. have recently documented a trend-increase of bone marrow (BM) CD3 + CD56 + T regulatory cells in myelodysplastic syndromes (MDS), with concomitant reduction of cytotoxic T cell activity favoring escape of leukemic blasts to immunological surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Since lymphocytes are mainly composed of B cells in CLL patients, the small percentage of T cells within the lymphocyte compartment appears to exhibit a preferential expansion of Treg and T R3-56 regulatory cell subsets, as a possible immune escape mechanism. Our data confirm the Treg expansion in CLL [78][79][80] and highlight an expansion also of the recently characterised regulatory T R3-56 population [51,52,81,82].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Since lymphocytes are mainly composed of B cells in CLL patients, the small percentage of T cells within the lymphocyte compartment appears to exhibit a preferential expansion of Treg and T R3-56 regulatory cell subsets, as a possible immune escape mechanism. Our data confirm the Treg expansion in CLL [78][79][80] and highlight an expansion also of the recently characterised regulatory T R3-56 population [51,52,81,82].…”
Section: Discussionsupporting
confidence: 87%
“…The role of altered HLA-G [78,80,81] expression in CLL is still controversial and of unclear prognostic significance [81]. Here, we demonstrated a preferentially increased expression of HLA-G on B cells, but not on T cells, from CLL patients with stable disease.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Serio et al conclude that BM T R3-56 frequency could be a flow-cytometry marker for MDS diagnosis, since consistently increased in high-risk MDS and AML, highlighting the role for this cell subset in promoting expansion of the dysplastic precursor/s with consequent ineffective myelopoiesis. 1 Serio et al data support the etiopathogenetic role of T R3-56 in MDS and the possible use of this population as diagnostic/prognostic marker of the disease. We previously suggested that type 1 diabetes (T1D) progression is associated with the loss of T R3-56 -dependent control of CTL effector functions 3 and, as commented by Serio et al, we highlighted the trend-increase of BM T R3-56 cells, with concomitant reduction of cytotoxic T-cell activity in MDS.…”
Section: What Is (Or Could Be) the Specific Clinical Relevance Of You...mentioning
confidence: 88%
“…To the Editor, Serio et al 1 show a significant reduction of CD3 + CD56 + regulatory T cells (T R3-56 ) in bone marrow (BM) of low-risk myelodysplastic subjects, as compared with the high-risk and the AML group; in addition, the BM frequency of mature granulocytes, a recognised marker of residual effective haematopoiesis, was observed to inversely correlate with T R3-56 in the MDS cohort. Such data are of great interest and confirm and extend, in an independent MDS cohort, the trend-increase of BM T R3-56 from very low/low risk to high/very high risk MDS and the inverse correlation with the cytotoxic T-cell (CTL) activity, likely fostering the escape of leukaemic blasts to immune-surveillance, by us recently described.…”
Section: What Is (Or Could Be) the Specific Clinical Relevance Of You...mentioning
confidence: 98%